Infinite Potential Barrier and Hydrostatic Pressure Effects on Impurity-Related Optical Absorption Spectra in GaAs Double Quantum Wells (2006)
ABSTRACT: Using the effective-mass approximation and the variational method, we have calculated the effects of hydrostatic pressure on the donor- and acceptor-related optical absorption spectra in symmetrical GaAs double quantum well structures. A central finite potential barrier and two infinite external barriers constitute the profile of the potential barrier considered for the wells. Our results are presented as a function of the well and barrier widths and hydrostatic pressure. For the pressure dependence we consider the Γ−X mixing in the central barrier layer. For symmetrical and infinite-external-barrier quantum wells, and depending on the sizes of the structure and the hydrostatic pressure, the donor-related spectra show three special structures, whereas for the acceptor one only two structures appear.